Comparison of muscle metabolomics between two Chinese horse breeds - Meng, Sihan; Zhang, Yanli; Lv, Shipeng; Zhang, Zhengkai; Liu, Xuexue; Jiang, Lin (Frontiers in Veterinary Science, 2023)
With their enormous muscle mass and athletic ability, horses are well positioned as model organisms for understanding muscle metabolism. There are two type of horse breeds with obvious difference in muscle content, while inhabited in the same region of China. Guanzhong (GZ) , an athletic breed with a larger body height (~148.7cm) while the Ningqiang pony (NQ) had a lower height and used for ornamental. The main objective of this study was to evaluate the breed specific mechanisms controlling muscle metabolism. In this study, we detect muscle glycogen, enzyme activities as well as LC-MS/MS untargeted metabolomics in gluteus medius muscle of six GZ and NQ horses, to explore differentiated metabolites that related two muscle development. As expect, the Glycogen content, citrate synthase and hexokinase activity of muscle were significantly higher in GZ horses. To alleviate the false positive rate, we used both MS1 and MS2 ions for metabolite classification and differential analysis. As a result, a total of 51,535 MS1 and 541 MS2 metabolites were identified, and they can separate these two groups. Notably, 40% of these metabolites were clustered into lipids and lipid-like molecules. Furthermore, 13 significant metabolites were differentially detected between GZ and NQ (Fold Change ≥2, Variable important in projection ≥1 and Qvalue ≤0.05). They are primarily clustered into glutathione metabolism (GSH, Pvalue =0.01), taurine and hypotaurine metabolism (Pvalue <0.05) pathways. Seven of the 13 metabolites were also found in thoroughbred racing horses, suggests that metabolites related to anti-oxidant, amino acid and lipid played a key role in development of skeleton muscle in horses. Those metabolites related to muscle development shed a light on racing horse routine maintenance and improvement of athletic performance.